Absence of a gender gap in survival. An analysis of the Italian registry for cystic fibrosis in the paediatric age - Viviani, Laura; Bossi, Anna; Assael, Baroukh Maurice (Journal of cystic fibrosis, 2011)
The existence of gender-related differences since childhood in survival of cystic fibrosis (CF) patients has been recently challenged. We evaluated the effect of gender on survival of 2293 CF patients born after 01/01/1988, followed up by 29 CF centres until 31/12/2004 and recorded in the Italian Registry for CF (IRCF). We observed similar annual mortality rates in females (3.59‰) and males (4.00‰), similar survival curves (log-rank test p = 0.64) and similar hazards of death (hazard ratio adjusted for presence of symptoms at diagnosis, meconium ileus, F508del mutation and age at diagnosis: 1.29, 95%CI: 0.60; 2.76). However, excess mortality due to CF was higher for females (5.9) than males (5.1). In our population CF females do not experience higher mortality than males but, due to the disease, they lose the expected survival advantage occurring in the general population at this age. We do not exclude, however, that differences in mortality will establish after adolescence.